A case study of education outreach coordinators in universities in Australia and New Zealand - Akiko Mori (Frontiers in Education)
IntroductionThe significance of STEM outreach in high school–university collaboration is well recognized; however, its ecosystem remains underdeveloped. Despite the criticality of Educational Outreach Coordinators (EOCs) in facilitating sustainable partnerships, their role in high school–university collaboration is underexplored. This study focuses on Queensland, Australia, and the North Island of New Zealand to explore the roles of coordinators who belong to universities.MethodSemi-structured interviews were conducted at four universities in February 2024. The results of four sets of 10 interviews were used to determine the positions and roles of coordinators at universities in charge of educational outreach to high schools, as well as their skills.ResultsAt the universities surveyed, professional coordinators were employed for educational outreach to high schools. The thematic analysis suggested that coordinators are proactively and centrally involved in various processes, such as relationship building, project development, oversight, evaluation, and personnel development. They contribute significantly to the success of these projects through strategic and autonomous management.DiscussionThe actual activities of coordinators of high school–university collaboration as university professionals have not been clarified in previous studies. Examples from the surveyed universities suggest that throughout high school–university collaboration, coordinators, in addition to teachers and learners, hold influence and play a vital role in the educational scene. Despite sample limitations, the findings provide a foundation for further exploration and institutional recognition of EOCs globally.